Unraveling the Photovoltaic, Mechanical, and Microstructural Properties and Their Correlations in Simple Poly(3‐pentylthiophene) Solar Cells. Issue 22 (27th May 2022) - Yang, Xuantong; Gao, Mengyuan; Bi, Zhaozhao; Liu, Yang; Xian, Kaihu; Peng, Zhongxiang; Qi, Qingchun; Li, Saimeng; Song, Jinsheng; Ma, Wei; Ye, Long
Abstract: The power conversion efficiency of polythiophene organic solar cells is constantly refreshed. Despite the renewed device efficiency, very few efforts have been devoted to understanding how the type of electron acceptor alters the photovoltaic and mechanical properties of these low‐cost solar cells. Herein, the authors conduct a thorough investigation of photovoltaic and mechanical characteristics of a simple yet less‐explored polythiophene, namely poly(3‐pentylthiophene) (P3PT), in three different types of organic solar cells, where ZY‐4Cl, PC71 BM, and N2200 are employed as three representative acceptors, respectively. Compared with the reference poly(3‐hexylthiophene) (P3HT)‐based solar cells, P3PT‐based devices, all perform more efficiently. Particularly, the P3PT:ZY‐4Cl blend exhibits the highest efficiency (ca. 10%) among the six combinations and outperforms the prior top‐performance system P3HT:ZY‐4Cl. Furthermore, the blend films based on N2200 exhibit a high crack‐onset strain of ∼38% on average, which is approximately 15‐ and 17‐times higher than those of ZY‐4Cl and PC71 BM, respectively. The microstructural origins for the above difference are well elucidated by detailed grazing incidence X‐ray scattering and microscopy analysis. This work not only underlines the potential of P3PT in prolific solar cell research but also demonstrates the superior tensile properties of polythiophene‐based all‐polymer blends for the preparation of stretchable solar cells. Abstract : The photovoltaic, mechanical, and microstructural characteristics of blend films based on poly(3‐pentylthiophene) (P3PT) and three different types of acceptors are thoroughly determined. The nonfullerene small‐molecule acceptor‐based blend exhibits the highest efficiency of ∼10%, while the blend based on polymer acceptor exhibits the best ductility. The results thus stress the rich potential of P3PT in nonfullerene solar cell research.